The role of ghrelin-responsive mediobasal hypothalamic neurons in mediating feeding responses to fasting - Bharath K. Mani; Sherri Osborne-Lawrence; Mathieu Mequinion; Sydney Lawrence; Laurent Gautron; Zane B. Andrews; Jeffrey M. Zigman (Elsevier, 2017)
Objective: Ghrelin is a stomach-derived hormone that affects food intake and regulates blood glucose. The best-characterized actions of ghrelin are mediated by its binding to and activation of the growth hormone secretagogue receptor (GHSR; ghrelin receptor). Adequate examination of the identity, function, and relevance of specific subsets of GHSR-expressing neurons has been hampered by the absence of a suitable Cre recombinase (Cre)-expressing mouse line with which to manipulate gene expression in a targeted fashion within GHSR-expressing neurons. The present study aims to characterize the functional significance and neurocircuitry of GHSR-expressing neurons in the mediobasal hypothalamus (MBH), as they relate to ghrelin-induced food intake and fasting-associated rebound hyperphagia, using a novel mouse line in which Cre expression is controlled by the Ghsr promoter. Methods: A Ghsr-IRES-Cre mouse line that expresses Cre directed by the Ghsr promoter was generated. The line was validated by comparing Cre activity in reporter mice to the known brain distribution pattern of GHSR. Next, the requirement of MBH GHSR-expressing neuronal activity in mediating food intake in response to administered ghrelin and in response to fasting was assessed after stereotaxic delivery of inhibitory designer receptor exclusively activated by designer drugs (DREADD) virus to the MBH. In a separate cohort of Ghsr-IRES-Cre mice, stereotaxic delivery of stimulatory DREADD virus to the MBH was performed to assess the sufficiency of MBH GHSR-expressing neuronal activity on food intake. Finally, the distribution of MBH GHSR-expressing neuronal axonal projections was assessed in the DREADD virus-injected animals. Results: The pattern of Cre activity in the Ghsr-IRES-Cre mouse line mostly faithfully reproduced the known GHSR expression pattern. DREADD-assisted inhibition of MBH GHSR neuronal activity robustly suppressed the normal orexigenic response to ghrelin and fasting-associated rebound food intake. DREADD-assisted stimulation of MBH GHSR neuronal activity was sufficient to induce food intake. Axonal projections of GHSR-expressing MBH neurons were observed in a subset of hypothalamic and extra-hypothalamic regions. Conclusions: These results suggest that 1) activation of GHSR-expressing neurons in the MBH is required for the normal feeding responses following both peripheral administration of ghrelin and fasting, 2) activation of MBH GHSR-expressing neurons is sufficient to induce feeding, and 3) axonal projections to a subset of hypothalamic and/or extra-hypothalamic regions likely mediate these responses. The Ghsr-IRES-Cre line should serve as a valuable tool to further our understanding of the functional significance of ghrelin-responsive/GHSR-expressing neurons and the neuronal circuitry within which they act.